Proceedings of the 12th International Conference on Advances in Computer Entertainment Technology 2015
DOI: 10.1145/2832932.2837017
|View full text |Cite
|
Sign up to set email alerts
|

Sensing the shape of canine responses to cancer

Abstract: We conducted a short study investigating the pressure patterns produced by cancer detection dogs via a caninecentered interface while searching samples of amyl acetate. We advance previous work by providing further insights into the potential of the approach for supporting and partly automating the practice of cancer detection with dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…Most animals do not have the means to communicate effectively with humans using any sort of vocal language and so the default means for understanding them is often the use of physiological and behavioural measurements and observations. With dogs, feedback on interfaces and interactive products has come from eye movements (Somppi, 2012), head gestures (Valentin et al, 2015, Hirskyj-Douglas andRead, 2014), nose reactions (Johnston-Wilder et al, 2015), mouth reactions (Robinson, 2014a(Robinson, , 2014b, heart and respiration rates (Mealin et al, 2015), cortisol levels (Rehn and Keeling, 2011;Geurtsen et al, 2015) and general posture analysis (Aspling et al, 2015), often via biotelemetry devices (Paci et al, 2016). Using these behaviours and actions as a form of communication, interfaces have been developed that allow dogs to react to stimuli from interactive tablet devices and use haptic technology (Moore Jackson et al 2013;Byrne et al, 2016).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Most animals do not have the means to communicate effectively with humans using any sort of vocal language and so the default means for understanding them is often the use of physiological and behavioural measurements and observations. With dogs, feedback on interfaces and interactive products has come from eye movements (Somppi, 2012), head gestures (Valentin et al, 2015, Hirskyj-Douglas andRead, 2014), nose reactions (Johnston-Wilder et al, 2015), mouth reactions (Robinson, 2014a(Robinson, , 2014b, heart and respiration rates (Mealin et al, 2015), cortisol levels (Rehn and Keeling, 2011;Geurtsen et al, 2015) and general posture analysis (Aspling et al, 2015), often via biotelemetry devices (Paci et al, 2016). Using these behaviours and actions as a form of communication, interfaces have been developed that allow dogs to react to stimuli from interactive tablet devices and use haptic technology (Moore Jackson et al 2013;Byrne et al, 2016).…”
Section: Related Workmentioning
confidence: 99%
“…Movement has been used for interactivity in the use of harnesses as input devices (Lemasson et al, 2015). Dogs have been shown to be able to provide system input through mouth gestures operating pulleys (Robinson, 2014a(Robinson, , 2014b and nose gestured operating plate interfaces (Johnston-Wilder et al, 2015;Mancini et al, 2014).…”
Section: Related Workmentioning
confidence: 99%
“…This delineation raises the question of what would dog communication look like. Whilst within our design fictions these are mostly visual or auditory, as noted by Lawson et al [24] these can also be olfactory where dogs communicate biological and emotive intentions [20]. Within the design fictions, participants often spoke about having numerous methods of the dog interacting to allow this choice of mechanism highlighting that there is more here to be investigated.…”
Section: Further Workmentioning
confidence: 94%
“…As noted within the ACI manifesto [9], the interaction can also be explored by improving the usability of systems as well as by creating a meaningful experience for the animal. This is evidenced in work that has studied how animals can input to technology [8,[41][42][43], how animals can be soothed or stimulated by technology [30,44,45] and how animals and humans can be connected through technology [4,6,38,40,46]. An interesting point within these intersections is the transferal of these technologies across species and across disciplines, that will also be addressed in this manuscript through modelling the technological system's space within ACI.…”
Section: What Is Interaction?mentioning
confidence: 99%
“…Grounded within the principles of animal-centred design, Johnston-Wilder et al [41] ( Figure 6) and Mancini et al [37] have created interfaces to provide supplementary information, in olfactory detection of cancer by dogs, using pressure plates. These studies, building from dogs' olfactory work, have found that an olfactory system is a possible interaction method within ACI, highlighting the potential of this approach as it allows for the dogs' natural behaviour while sniffing the samples.…”
Section: Olfactory Interfacesmentioning
confidence: 99%